Analisis Perilaku Golput Dikalangan Masyarakat Dan Aspek Hukum Golput Dalam Pelaksanaan Pemilihan Umum - Jayanti, Wilda Dwi; Putri, Vianka Maulidya (Peneliti.net, 2024)
In the implementation of general elections in Indonesia, there is always the involvement of white-skinned voters, commonly referred to as